1998
DOI: 10.1016/s0039-6028(98)00120-4
|View full text |Cite
|
Sign up to set email alerts
|

The reconstruction of Rh(001) upon oxygen adsorption

Abstract: We report on a first-principles study of the structure of O/Rh(001) at half a monolayer of oxygen coverage, performed using density-functional theory. We find that oxygen atoms sit at the center of the black squares of a chess-board, c(2 × 2), pattern. This structure is unstable against a rhomboid distortion of the black squares, which shortens the distance between an O atom and two of the four neighboring Rh atoms, while lengthening the distance with respect to the other two. We actually find that the surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…3) at the 0.5 monolayer (ML) coverage of the surface carbon over Pd(100). The clock-type surface reconstruction has been observed previously using both STM experiments and theoretical calculations on Rh(100) and Ni(100) upon adsorption of carbon, oxygen and nitrogen atoms [41][42][43][44][45][46][47].…”
Section: Resultssupporting
confidence: 68%
“…3) at the 0.5 monolayer (ML) coverage of the surface carbon over Pd(100). The clock-type surface reconstruction has been observed previously using both STM experiments and theoretical calculations on Rh(100) and Ni(100) upon adsorption of carbon, oxygen and nitrogen atoms [41][42][43][44][45][46][47].…”
Section: Resultssupporting
confidence: 68%
“…It is interesting to note that the Ni(100)-(2Â2)p4g-2N STM image exhibits two orientations of the depressions. With slight deviation, one is along the [10] direction and the In 1998, Alfe et al [160,161,277] suggested an alternative (Fig. 20d) for the Rh(001)-c(2Â2)p4g-2O second phase.…”
Section: à2mentioning
confidence: 96%
“…At low CO coverage all CO ads is inside the p(2ϫ2) and reacts to CO 2 between 300 and 400 K. At higher coverages of CO ads reaction occurs in the c(2ϫ2), with a sharp CO 2 formation peak at 280 K. We wonder if this peak is associated with the lifting of the well-documented clockwise-anticlockwise reconstruction of the Rh͑100͒ surface upon saturation with O. 32,[60][61][62] The splitting up of the 350 K CO 2 formation into a lower and a higher temperature CO 2 formation channel with increasing CO coverage as seen in the right part of Fig. 2 is due to depletion of oxygen atoms.…”
Section: B Different Co 2 Formation Channels On Rh"110…mentioning
confidence: 99%